Risk factors for high caries experience among 16 year old school in Tumpat district, Kelantan - Abdullah, Nizam (2005)
The objectives of this study were to determine the prevalence of dental caries, the differences in knowledge, attitude and practice (KAP) level among caries experience group as well as to determine the associated factors for caries and high caries experience among 16-year-old school children in Tumpat district. The first part was a cross-sectional study to determine the prevalence of caries and the second stage of this study was a case-control study. The outcome of the study revealed that the prevalence of dental caries was high among the study group in Tumpat. Low educational level of parents, unhealthy deciduous teeth and salivary factors were important factors determining the caries experience. Positive dental attitude and low frequency of sugar intake had protective effect against caries experience. The knowledge on factors associated with caries experience is very useful in planning effective preventive dental program especially for group experiencing high caries.